Vitamin D3 supplementation attenuates the early stage of mouse hepatocarcinogenesis promoted by hexachlorobenzene fungicide. (September 2017) - Romualdo, Guilherme R.; Goto, Renata L.; Fernandes, Ana A.H.; Cogliati, Bruno; Barbisan, Luis F.
Abstract: Hexachlorobezene (HCB), a fungicide widely distributed in the environment, promotes the development of hepatocellular preneoplastic lesions (PNL) and tumors in rodents. In contrast, vitamin D3 (VD3 ) supplementation presents a potential role for the prevention/treatment of chronic liver diseases. Thus, we investigated whether VD3 supplementation attenuates the early stage of HCB-promoted hepatocarcinogenesis. Female Balb/C mice were injected a single dose of diethylnitrosamine (DEN, 50 mg/kg) at postnatal day 15. From day 40 onwards, mice were fed with a standard diet containing 0.02% HCB alone or supplemented with VD3 (10, 000 or 20, 000 IU/Kg diet) for 20 weeks. Untreated mice were fed just standard diet. After this period, mice were euthanized and liver and serum samples were collected. Compared to the untreated group, DEN/HCB treatment decreased total hepatic glutathione levels and glutathione peroxidase (GSH-Px) activity while increased lipid peroxidation, p65 protein expression, cell proliferation/apoptosis and the PNL development. In contrast, dietary VD3 supplementation enhanced vitamin D receptor (VDR) protein expression, total glutathione levels and GSH-Px activity while diminished lipid hydroperoxide levels. Also, VD3 supplementation decreased p65 protein expression, hepatocyte proliferation, the size and the liver area occupied by PNL. Therefore, our findings indicate that VD3 supplementation attenuates the early stage of HCB-promoted hepatocarcinogenesis. Graphical abstract: Highlights: VD3 supplementation attenuates HCB-promoted hepatocarcinogenesis. VD3 reduces the oxidative stress by restoring total GSH levels and GSH-Px activity. VD3 reduces hepatocyte proliferation (Ki-67) by decreasing NF-κB (p65) expression. VD3 decreases the size and the liver area occupied by preneoplastic lesions.